Expanding the category "human" nonhumanism, posthumanism, and humanistic psychology - Whitehead, Patrick M., 1986- (Lexington Books, 2018)
In Expanding the Category ""Human"": Nonhumanism, Posthumanism, and Humanistic Psychology Patrick Whitehead argues that humanistic psychology must continue its sixty-year-old project of openness of inquiry and acceptance of human beings in order to stay relevant in this ever changing world.